The Effect of Compensation and Competence on Discipline and its Impact on Employee Performance in the Search and Relief Office Class B Jambi - Kornelis, Kornelis; Zahari, M.; Rozi Yamali, Fakhrul (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study investigates the roles of compensation, work competence, and work discipline in influencing employee performance at the Jambi Class B Search and Rescue Office. It also examines how compensation and competence impact employee performance indirectly through work discipline. Utilizing descriptive verification research methods, the study focuses on the relationships between these variables. The research employs Partial Least Squares (PLS) analysis. Survey results reveal that the compensation score is 1384, indicating a satisfactory level. Work competence is rated highly, with a score of 2295. Work discipline also scores high at 1877, while employee performance is rated even higher at 3241. The findings indicate that both compensation and work competence positively and significantly impact work discipline. Additionally, compensation, competence, and discipline all have a positive and significant effect on employee performance. Notably, compensation and competence also positively influence employee performance through their effects on work discipline at the Jambi Class B Search and Rescue Office.